Safety of Tranexamic Acid in Hip and Knee Arthroplasty in High-risk Patients. (15th April 2021) - Poeran, Jashvant; Chan, Jimmy J.; Zubizarreta, Nicole; Mazumdar, Madhu; Galatz, Leesa M.; Moucha, Calin S.
Abstract : Background: With increasing use of tranexamic acid in total hip and knee arthroplasties, safety concerns remain. Using national claims data, this study examined tranexamic acid use in patients with preexisting comorbidities. The hypothesis was that tranexamic acid use is not associated with increased complication risk in hip and knee arthroplasty patients with comorbidities. Methods: Among 765, 011 total hip/knee arthroplasties (2013 to 2016, Premier Healthcare claims), tranexamic acid use was assessed in three high-risk groups: group I with patients with a history of venous thromboembolism, myocardial infarction, seizures, or ischemic stroke/transient ischemic attack (n = 27, 890); group II with renal disease (n = 44, 608); and group III with atrial fibrillation (n = 45, 952). The coprimary outcomes were blood transfusion and new-onset "composite complications" (venous thromboembolism, myocardial infarction, seizures, and ischemic stroke/transient ischemic attack). Associations between tranexamic acid use and outcomes were measured separately by high-risk group. The odds ratios and Bonferroni-adjusted 99.9% CIs are reported. Results: Overall, 404, 974 patients (52.9%) received tranexamic acid, with similar frequencies across high-risk groups I (13, 004 of 27, 890 [46.6%]), II (22, 424 of 44, 608 [50.3%]), and III (22, 379 of 45, 952 [48.7%]). Tranexamic acid use was associated with decreased odds of blood transfusion in high-risk groups I (721 of 13, 004 [5.5%] vs. 2, 293 of 14, 886 [15.4%]; odds ratio, 0.307; 99.9% CI, 0.258 to 0.366), group II (2, 045 of 22, 424 [9.1%] vs. 5, 159 of 22, 184 [23.3%]; odds ratio, 0.315; 99.9% CI, 0.263 to 0.378), and group III (1, 325 of 22, 379 [5.9%] vs. 3, 773 of 23, 573 [16.0%]; odds ratio, 0.321; 99.9% CI, 0.266 to 0.389); all adjusted comparisons P < 0.001. No increased odds of composite complications were observed in high-risk group I (129 of 13, 004 [1.0%] vs. 239 of 14, 886 [1.6%]; odds ratio, 0.89, 99.9% CI, 0.49 to 1.59), group II (238 of 22, 424 [1.1%] vs. 369 of 22, 184 [1.7%]; odds ratio, 0.98; 99.9% CI, 0.58 to 1.67), and group III (187 of 22, 379 [0.8%] vs. 290 of 23, 573 [1.2%]; odds ratio, 0.93; 99.9% CI, 0.54 to 1.61); all adjusted comparisons P > 0.999. Conclusions: Although effective in reducing blood transfusions, tranexamic acid is not associated with increased complications, irrespective of patient high-risk status at baseline. Abstract : National administrative data from more than 500 hospitals and 40, 000 patients demonstrate that approximately half of high-risk patients receive tranexamic acid, similar to non–high-risk patients. Tranexamic acid use in high-risk patients undergoing lower-extremity arthroplasty is associated with fewer transfusions. Tranexamic acid use is not associated with venous thromboembolism, myocardial infarction, seizures, ischemic strokes, or transient ischemic attacks. Supplemental Digital Content is available in the text.